Bus rail transit as an optimum solution for Majlis Bandaraya Melaka Bersejarah future public transportation demand - Nurulain , Zaini (2012)
Transport is a key requirement of human travel or movement from one place to another place without taking into account the distance to the destination. Rail service system bus, which was introduced by the state government of Melaka is one of the efforts to upgrade the existing public transport facilities. Shuttle bus service available is not sufficient demand for the use of an attempt to accommodate a public bus in the present and the future of public services. The purpose of this study was to obtain user feedback on their perception of public transport services. In addition, the purpose of this study was to examine the system of rail-bus service (Melaka Tram), which will start operating in Melaka next year (2013). Questionnaires were distributed to the respondents and analyzed statistically. As a whole, the results showed that respondents gave a poor perception of the quality of public bus services in Malacca. In addition, these studies also review how rail bus components can be the backbone of the existing public transport in Melaka. Results from this study indicate that the problem of cloud services (shuttle bus) is not available on time and also not very convenient to the user. In addition, the rail-bus components are designed to increase the quality of public bus services in Melaka is the path rail-bus, ticket payment system that uses machines, stations and intelligent information systems for users' rail-bus. At the end of the study, there are some suggestions to improve the public transportation in Melaka to make sure that the levels of services are same with other public transportation in the other developed countries. Among its recommendations is to apply the bus rail component in the management of the existing public bus. This is because not only can attract the attention of the public to use public services but also can reduce the traffic congestion in Melaka.